AP-1-Targeted Anti-Inflammatory Activities of the Nanostructured, Self-Assembling S5 Peptide - Woo Seok Yang; Young-Jin Son; Mi-Yeon Kim; Soochan Kim; Jong-Hoon Kim; Jae Youl Cho (Hindawi Limited, 2015)
Peptide-based therapeutics have received increasing attention in medical research. However, the local delivery of such therapeutics poses unique challenges. Self-assembling peptides that use decorated nanofibers are one approach by which these therapeutics may be delivered. We previously found that the self-assembling K5 peptide affects the anti-inflammatory response. The aim of the present study was to investigate another self-assembling peptide, S5. Unlike the K5 peptide which has a positive charge, the S5 peptide has a free hydroxyl (-OH) group. We first examined whether the S5 peptide regulates the inflammatory response in primary cells and found that the S5 peptide reduced the production of prostaglandin E2 (PGE2) and tumor necrosis factor (TNF)-α in lipopolysaccharide- (LPS-) treated bone marrow-derived macrophages. Moreover, the S5 peptide significantly downregulated cyclooxygenase- (COX-) 2, TNF-α, and interleukin- (IL-) 1β expression by blocking the nuclear translocation of c-Jun. Consistent with this finding, the S5 peptide diminished the activation of inflammatory signaling enzymes related to p38. The S5 peptide also inhibited the formation of the p38/c-Jun signaling complex in RAW264.7 cells. Similarly, p38 and MKK3/6 were inhibited by the S5 peptide in LPS-activated peritoneal macrophages. Taken together, these results strongly suggest that the S5 peptide could exert anti-inflammatory effects by inhibiting the c-Jun/p38 signaling pathway.